Valorisation of biomass and diaper waste into a sustainable production of the medical mushroom Lingzhi Ganoderma lucidum - Khoo, Shing Ching; Ma, Nyuk Ling; Peng, Wan Xi; Ng, Kah Kei; Goh, Meng Shien; Chen, Hui Ling; Tan, Suat Hian; Lee, Chia Hau; Luang-In, Vijitra; Sonne, Christian (Elsevier, 2021)
Global solid waste is expected to increase by at least 70% annually until year 2050. The mixture of solid waste including food waste from food industry and domestic diaper waste in landfills is causing environmental and human health issues. Nevertheless, food and diaper waste containing high lignocellulose can easily degrade using lignocellulolytic enzymes thereby converted into energy for the development and growth of mushroom. Therefore, this study explores the potential of recycling biomass waste from coffee ground, banana, eggshell, tea waste, sugarcane bagasse and sawdust and diaper waste as raw material for Lingzhi mushroom (Ganoderma lucidum) cultivation. Using 2% of diaper core with sawdust biowaste leading to the fastest 100% mushroom mycelium spreading completed in one month. The highest production yield is 71.45 g mushroom; this represents about 36% production biological efficiency compared to only 21% as in commercial substrate. The high mushroom substrate reduction of 73% reflect the valorisation of landfill waste. The metabolomics profiling showed that the Lingzhi mushroom produced is of high quality with a high content of triterpene being the bioactive compounds that are medically important for treating assorted disease and used as health supplement. In conclusion, our study proposed a potential resource management towards zero-waste and circular bioeconomy for high profitable mushroom cultivation.